The Effect of Local Tax, Local Retribution, Restricted local assets Management, and General Allocation Funds on Regency and Municipal Capital Expenditures in - Dede Chumairoh; Andi; Mukhtar (Management Science Research Journal, 2022)
This paper examines the effect of Local Tax, Local Retribution Restricted local assets Management, and general allocation of funds on regencies and municipal capital expenditures in the province of Banten for the 2015-2019 period. The research sample is the district and city governments in Banten Province, totaling 8 districts and cities consisting of 4 districts and 4 cities in the 2015-2019 Local Budget Revenue Realization Report (LRAPBD) of the Banten provincial government. Through the purposive sampling technique, the results show that the variables of local taxes and retribution have an effect on capital expenditures, while the variables of separate local wealth management and general location funds have no effect